A novel approach to achieving modular retrovirus clearance for a parvovirus filter. (24th October 2013) - Stuckey, Juliana; Strauss, Daniel; Venkiteshwaran, Adith; Gao, Jinxin; Luo, Wen; Quertinmont, Michelle; O'Donnell, Sean; Chen, Dayue
<x xml:space="preserve">Abstract</x> Viral filtration is routinely incorporated into the downstream purification processes for the production of biologics produced in mammalian cell cultures (MCC) to remove potential viral contaminants. In recent years, the use of retentive filters designed for retaining parvovirus (∼20 nm) has become an industry standard in a conscious effort to further improve product safety. Since retentive filters remove viruses primarily by the size exclusion mechanism, it is expected that filters designed for parvovirus removal can effectively clear larger viruses such as retroviruses (∼100 nm). In an attempt to reduce the number of viral clearance studies, we have taken a novel approach to demonstrate the feasibility of claiming modular retrovirus clearance for Asahi Planova 20N filters. Porcine parvovirus (PPV) and xenotropic murine leukemia virus (XMuLV) were co‐spiked into six different feedstreams and then subjected to laboratory scale Planova 20N filtration. Our results indicate that Planova 20N filters consistently retain retroviruses and no retrovirus has ever been detected in the filtrates even when significant PPV breakthrough is observed. Based on the data from multiple in‐house viral validation studies and the results from the co‐spiking experiments, we have successfully claimed a modular retrovirus clearance of greater than 6 log10 reduction factors (LRF) to support clinical trial applications in both USA and Europe. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:79–85, 2014